Formal [2+1] annulation (Spiro-Cyclopropanation) reaction between sulfur ylides derived from baylis-hillman bromides and arylidene indane-1,3-dione - Roy, Suparna; Piradhi, Venkatesh (Chemistryselect, 2017)
The sulfonium salts derived from the Baylis-Hillman bromides have been successfully employed for the selective cycloproporanation of arylidene indane-1,3-diones to synthesize densely substituted spiro-cyclopropanes in good to excellent yields (upto 94%). Products were obtained mostly in 1:1 diastereomeric ratio and were isolated in pure form. Diastereoselectivity has been improved by using suitably substituted starting materials. In this case a formal [2+1] annulation reaction competes over a probable [3+2] cycloaddition reaction. The reaction proceeds through a Michael initiated ring closure process of S-ylides to the activated olefins for the formation of structurally strained spiro-cyclopropanes.